ILife '09 - Cohen, Michael E. (Peachpit Press, 2009)
An overview of the multimedia applications of Apple's iLife covers the fundamentals of iPhoto, iMovie, iDVD, GarageBand, and iWeb.
"Apple certified.". - "IPhoto, iMovie, GarageBand, iWeb, iDVD"--Cover. - Includes index. - Print version record
Keywords: iLife; iMovie; Interactive multimedia; Macintosh (Computer); Digital video; Video recordings -- Computer programs; ILife; IMovie; Multimédias interactifs; Macintosh (Ordinateur); Vidéo numérique; Vidéos; Logiciels; Video recordings; Computer programs; Electronic resource